Adenosinergic Signaling Alters Natural Killer Cell Functional Responses - Chambers, Andrea M.; Wang, Jiao; Lupo, Kyle B.; Yu, Hao; Atallah Lanman, Nadia M.; Matosevic, Sandro (Frontiers in Immunology, 2018)
Adenosine is a potent immunosuppressive purine metabolite contributing to the pathogenesis of solid tumors. Extracellular adenosine signals on tumor-infiltrating NK cells to inhibit their proliferation, maturation and cytotoxic function. Cytokine priming imparts upon NK cell distinct activation statuses, which modulate NK anti-tumor immunity and responses to purinergic metabolism. Here, for the first time, we investigated human NK cell responses to adenosinergic signaling in the context of distinct cytokine priming programs. NK cells were shown to be hyper-responsive to adenosine when primed with IL-12 and IL-15 compared to IL-2, exhibiting enhanced IFN-γ expression from CD56bright and CD56dim subsets while modulating the expression of activation marker NKG2D. These responses resulted in signaling that was dependent on mTOR. Adenosine induced upregulation of transcriptional signatures for genes involved in immune responses while downregulating cellular metabolism and certain protein synthesis functions that correlate to inhibited oxidative phosphorylation and glycolysis. Overall, our findings show that adenosine acts on specific cellular pathways rather than inducing a broad inhibition of NK cell functions. These responses are dependent on cytokine priming signatures and are important in designing therapeutic interventions that can reprogram NK cell immunometabolism for improved immunotherapies of solid tumors.